Magnetic Resonance Spectroscopy May Help Diagnose Sporadic Meningioangiomatosis Associated With Meningioma: A Case Report - Liu, Linfeng; Liang, Feng (Frontiers in Neurology, 2022)
Herein, we have presented the clinical features of meningioangiomatosis associated with meningioma, which is considered to be a rare neoplastic lesion. Magnetic resonance spectroscopy (MRS) demonstrated a remarkably decreased N-acetylaspartate peak and an increase in the choline peak of the lesion, suggesting neuronal injury and active cell proliferation. These findings substantially differed from those observed in the case of pure meningioangiomatosis.